Ribbed double pipe heat exchanger: Experimental analysis - Al-Kayiem, H.H. (WITPress, 2014)
Convection heat transfer can be enhanced by imposed turbulence in the annular flow of a double pipe heat exchanger. This paper presents and discusses the results obtained from experimental measurement by the installation of turbulence promoters, having rib configuration, on the inner surface of the cold flow annulus of a counter flow double-pipe heat exchanger. The promoters have been selected with ribâs height to hydraulic diameter, e/Dh equal to 0.107 and two pitch to height ratios, p/e equal to 10 and 15. The annular cold flow was investigated within Reynolds number range of 2000 to 20000. The measured data enabled us to estimate the friction factor, Reynolds number and Stanton number of each case in order to analyse the performance enhancement of the double pipe heat exchanger. The results showed that enhancement in the heat transfer, in terms of the Stanton number, was combined with a small penalty in the pressure drop, which was due to an increase in the friction factor values. Within the tested ranges of e/Dh and Re, the performance index indicated enhancement of about 1.3 to 1.8 at pitch to p/e = 10. It is recommended to investigate more cases of ribâs heights and installation in the hot fluid flow side. Â© 2014 WIT Press.